Implementation of E-Book and Textbook Learning Media to Grow Conservation Character and Digital Literacy Ability on Science Subjects in Coastal Schools - Mardin, Herinda; Rasyid, Tiska; Katili, Abubakar Sidik (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2024)
This study aims to determine the application of the use of e-book learning media to students in class VI SDN 04 Popayato which is an experimental class 1 and the application of the use of textbook learning media to students in class VI SDN 09 Popayato which is an experimental class 2 to foster the character of conservation and digital literacy skills in science subjects in coastal schools. This research method uses a quasi-experimental design, with a true experimental design in the form of a Posttest-Only Control Design. Data collection techniques include observation, questionnaires, and documentation. Data analysis used statistical analysis consisting of questionnaire percentages and independent t-tests. The results of the research on students in class VI SDN 04 Popayato which is an experimental class 1 showed an average percentage of the conservation character questionnaire of 86.82% and the digital literacy questionnaire was 88.55%, while students in class VI SDN 09 Popayato which was an experimental class 2 showed an average -the average percentage of the conservation character questionnaire is 70.60% and the digital literacy questionnaire is 72.03%, the results of the t-test of the conservation character questionnaire and the digital literacy questionnaire show 0.00 > 0.05 meaning there is a difference in growing conservation character and digital literacy skills in natural science subjects at school coast.